Implementasi Artificial Intelligence (AI) dalam Pembelajaran Pendidikan Agam Islam di Era Digitalisasi Sekolah - Niken Juliani; Arif Hidayat; Neni Neni (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
The rapid development of digital technology, particularly Artificial Intelligence (AI), has significantly influenced educational practices, including Islamic Religious Education (PAI). A major issue lies in how AI can be implemented effectively without undermining the spiritual, moral, and character-building values that are central to Islamic education. This study aims to examine the implementation of Artificial Intelligence in Islamic Religious Education learning in the era of school digitalization, focusing on its concepts, forms of application, teachers’ roles, benefits, as well as challenges and ethical considerations. This research employs a qualitative library research method. Data were collected from reputable academic journals, scholarly books, proceedings, and relevant official documents, and analyzed using content analysis techniques through data reduction, data display, and conclusion drawing. The findings indicate that AI has substantial potential to enhance PAI learning through personalized learning systems, adaptive learning media, and data-driven assessments. However, its implementation requires strong teacher supervision, adequate digital literacy, and alignment with Islamic values to prevent the marginalization of teachers’ moral and spiritual roles. In conclusion, Artificial Intelligence serves as a supportive tool in Islamic Religious Education and must be applied wisely, ethically, and in accordance with the fundamental objectives of Islamic education.